Metaphors of the future and the power of images in the British TV drama Spooks. (November 2016) - Izgarjan, Aleksandra; Djurić, Dubravka
Highlights: Construction of narratives about future in the television series Spooks involving macro-securitization and terrorism Dominant discourses of manageable future and future as an apocalypse (avoidable through individual efforts). CLA methodology reveals competing worldviews on future of the western alliance and terrorist groups featured in Spooks . Deconstruction of the series' complex narratives gives space to its alternative perspectives of future. Abstract: Our analysis of metaphors of the future in the British TV drama Spooks is situated within the phenomenon of television as a complex narrative and global media product at the time of the proclaimed war on terror. We claim that the conceptualization of the future is shaped by the notion of the conflicts between civilizations, in which various Others are produced by media and military discourses as a threat to western civilization. The dominant discourses in Spooks involve the manageable future (as a destination and a framework) and the future as judgment and apocalypse (which can be avoided through the process of macro-securitization that relies on predictive analysis and the efforts of competent individuals). We explore the anticipatory aspect of the series since it predicted geopolitical trends such as 7/7, the Ukrainian crises and the negative perception of Russia. Spooks deconstructs the notion of a homogenous Western alliance and exposes the hypocrisy of the war on terror which includes the violation of civil rights. Our analysis suggests that the series has transformative potential by offering alternative future perspectives of the different sides in the conflict.